Leachate pollution pathways in an arid coastal megacity: salinity, organics, and LPI–GIS mapping for Karachi - Azizullah Channa; Muhammad Yousuf Jat Baloch; Rasool Bux Mahar; Hongtao Wang (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

From barns to atmosphere: Pakistan's livestock manure-derived NH3, N2O, and CH4 emissions (1961–2022) and cleaner production pathways - Syed Qasim Ali Shah; Noor Haleem; Chaudary Muhammad Haris; Leena Khan; Yousuf Jamal; Humayoun Akram; Xufei Yang (Journal of Cleaner Production, 2026)

Elucidating the role of ammonia doping in modulating combustion dynamics in ethane fuel-rich jet flames - Bipro Gain; Muhammad Bilal; Yun-Fan Wang; Ahmed E. Mansy; Muhammad Yousuf; Kai-Ru Jin; Du Wang; Boyang Su; Aqsa Liaqat; Mohammed Khalil; Zhi-Min Wang; Qingli Li; et al. (Fuel, 2026)

Machine and deep learning for sentinel-based land use and land cover change detection: a systematic review and future outlook - Anam Nigar; Yang Li; Muhammad Yousuf Jat Baloch; Sedra Shafi; Abdullahi Garba Usman (Environmental Monitoring and Assessment, 2026)

Entropy generation in electroosmotic cilia-induced Jeffrey fluid flow through an axisymmetric tube with slip effects - Muhammad Yousuf Rafiq; Zaheer Abbas; Hafiz Shahzad; Sharia Bashir (Dynamics of Atmospheres and Oceans, 2026)

Nafion-assisted n-TOPCon bottom cells integrated with FAPbI₃ perovskite top cells for high-efficiency four-terminal tandem solar cell under rear-albedo illumination - Alamgeer; Hyunseo Lee; Shurouq Abdulqadir Mohammed; Muhammad Quddamah Khokhar; Hasnain Yousuf; Sangheon Park; Jaeki Jeong; Junsin Yi (Chemical Engineering Journal, 2026)

Reservoir Quality Evolution in the Permian Wargal Carbonate Ramp, Western Salt Range, Pakistan - Bilal Ahmed; Huafeng Tang; Shahzad Bakht; Muhammad Yousuf Jat Baloch (Journal of Marine Science and Engineering, 2026)
The Permian Wargal Formation of the western Salt Range preserves a shallow marine carbonate-ramp succession, in which heterogeneity reflects coupled depositional architecture, facies-selective diagenesis, and deformation-related structural compartmentalisation of the Wargal interval. This study integrates balanced restoration with stratigraphic logging, microfacies analysis, paragenetic reconstruction, and quantitative pore-network topology to evaluate how stratigraphic packaging and diagenetic overprint govern connected pathway development within a structurally partitioned fold–thrust setting. Balanced restoration of a representative transect yields 1.1336 km of minimum tectonic shortening (18.7%) and indicates shortening shared between thrust slip and distributed folding, providing an admissible geometric framework for assessing compartmentalisation. The Wargal succession is ~130 m thick and organised into three carbonate packages bounded by laterally persistent argillaceous marker intervals (~21–23 m and ~98–105 m), with grain-supported shoal to shoal-margin facies dominating intervening units. Diagenesis is strongly facies-selective; grain-supported microfacies record progressive calcite cementation that occludes pore throats, whereas mud-supported facies retain microporosity but are preferentially modified by neomorphism, compaction, and pressure-solution fabrics. Image-based analysis of 20 thin-section fields of view shows that pore connectivity varies systematically among microfacies and that a connectivity-weighted index (Iconn) covaries more closely with skeleton-derived connectivity than with segmented areal porosity (ϕ2D=0.124–9.750%). The combined results quantify the decoupling between pore volume and connectivity and provide a basis for predicting reservoir-quality evolution from facies architecture, diagenetic sequence, and structural segmentation, with direct relevance to subsurface characterisation of marine carbonate successions in hydrocarbon systems.

Nonlinear analysis of thermo-magneto slip flow of Jeffery fluid in a wavy curved channel - Maham Mujahid; Mounirah Areshi; Zaheer Abbas; Muhammad Yousuf Rafiq; Ibrahim E. Elseesy (Dynamics of Atmospheres and Oceans, 2026)

Computationally guided synthesis and biological profiling of chalcones as antioxidant and anti-inflammatory activities - Hafiz Aamir Ali Kharl; Muhammad Naeem; Shakira Ghazanfar; Arifa Mehreen; Hasnain Haider; Sumel Ashique; Sabina Yasmin; Fatimah M. Al-Salem; Md Yousuf Ansari (Inflammopharmacology, 2026)

Heavy Metals Bioaccumulation in Riparian Vegetation: A Multi-Species Biomonitoring Framework Using Total X-Ray Reflection Fluorescence Spectroscopy - Shakeel Ahmed Talpur; Simonetta Cristina Di Simone; Aziz Ahmed; Hafeez Ahmed Talpur; Muhammad Yousuf Jat Baloch; Francesco Stoppa; Luigi Menghini; Beatrice Maria Sole Giambastiani; Gianluigi Rosatelli (Environmental Processes, 2026)
Heavy metal contamination in Mediterranean riparian ecosystems presents serious risks to biodiversity and human health, requiring innovative biomonitoring methods for polluted watersheds. This study developed a comprehensive biomonitoring framework for an industrially impacted Mediterranean river basin, with approximately 100,000 tons of contaminated waste in landfills from decades of metallurgical processing. We investigated heavy metal bioaccumulation patterns in five taxonomically diverse native riparian species ( Equisetum arvense , Laurus nobilis , Rubus ulmifolius , Sambucus nigra , and Salix alba ) across contaminated and reference sites using Total Reflection X-ray Fluorescence (TXRF) spectroscopy. TXRF was validated against Inductively Coupled Plasma Atomic Optical Spectroscopy (ICP-AOS) using standard reference materials, demonstrating superior sensitivity for trace element detection in plant matrices. Heavy metal concentrations varied significantly among species and sites in riparian vegetation, with Fe (23.14 ± 5.21 mg/kg), Mn (2.74 ± 0.89 mg/kg), and Cr (3.33 ± 1.12 mg/kg) showing the highest accumulation. Laurus nobilis appeared as a multi-metal hyperaccumulator with the highest Pollution Load Index (PLI = 2.67) and exceptional accumulation of Cr (14.74 mg/kg) and Fe (63.64 mg/kg). Statistical analysis (Kruskal-Wallis test, p < 0.05) confirmed that Mn and Cr represented primary anthropogenic pollutants, with contaminated sites showing 2.20-fold and 1.92-fold increases, respectively. Principal Component Analysis revealed distinct co-accumulation networks, with Fe-Cr-Ni-Cu forming synchronized uptake mechanisms, while Mn operated independently. Biogeochemical ratio analyses (Fe/Zn, Cu/Mn) provided sensitive contamination indicators, detecting physiological stress beyond simple concentration measurements. Results support species-specific phytoremediation strategies aligned with UN Sustainable Development Goals, with Laurus suitable for multi-metal extraction and Equisetum for Mn-specific remediation, advancing sustainable environmental management in industrially impacted Mediterranean watersheds.

Intraspecific and interspecific variation of Salvadora species (S. oleoides Decne. and S. persica L.) along an aridity gradient in dryland ecosystems - Ummar Iqbal; Atta Hussain Sahir; Muhammad Sharif; Abdul Wahab; Mehboob Ahmad; Muhammad Yousuf; Sadaf Rafiq; Sana Abid (Trees, 2026)

Microstructural adaptations of snow bush (Aerva javanica (Burm.f.) Juss. Ex Schult.) in desert ecosystems - Sana Abid; Ummar Iqbal; Muhammad Sharif; Sadaf Rafiq; Aisha Sana; Abdul Wahab; Mehboob Ahmad; Muhammad Yousuf (The Science of Nature, 2026)

Native Plants as Living Sensors: Tracking Air Pollution in Industrial Zones - Muhammad Sharif; Ummar Iqbal; Abdul Wahab; Muhammad Yousuf; Mehboob Ahmad; Muhammad Sharjeel Arif (International Journal of Environmental Research, 2026)

Caffeoylquinic acid derivatives isolated from Tussilago farfara L. as potential anti-leishmanial agents; in vitro and in silico studies - Izaz Ahmad; Salar Hafez-Ghoran; Muhammad Yousuf; Humaira Zafar; Atia-tul- Wahab; Sammer Yousuf; Mushtaq Ahmad; Inam Gul; Bates Kudaibergenova; M. Iqbal Choudhary (Natural Product Research, 2026)

Fate and transport of viruses in the subsurface environment: A systematic review of pollution pathways in saturated and unsaturated porous media - Muhammad Yousuf Jat Baloch; Purnima Baidya; Manita Aryal; Muhammad Moeen-ud-din; Liu Yang; Javed Iqbal; Mariusz Ptak; Predrag llić; Chunguang Liu (Environmental Research, 2026)

Flavonolignans from Lannea acida A. Rich. as potential antileishmanial agents - Muhammad Aamer; Muhammad Kamran; Muhammad Yousuf; Kayode Muritala Salawu; Humaira Zafar; Atia-tul Wahab; M. Iqbal Choudhary; Farooq-Ahmad Khan; Yan Wang (Natural Product Research, 2025)

Phenotypic Characterization and Adaptability of Wild Sugarcane to Diverse Pedospheric and Atmospheric Conditions - Ummar Iqbal; Mehboob Ahmad; Muhammad Sharif; Abdul Wahab; Muhammad Yousuf; Sadaf Rafiq; Sana Abid (Tropical Plant Biology, 2025)

Interfacial defect mitigation in HJT bottom cells for improved efficiency of monolithic perovskite/Si tandem solar cells - Mengmeng Chu; Hasnain Yousuf; Shanshan Gao; Maha Nur Aida; Xiaobo Wang; Muhammad Quddamah Khokhar; Junsin Yi (Chemical Engineering Journal, 2025)

Exploring nonstructural NS5B protein to design a multi-epitope-based vaccine against HCV: immuno-informatics approach - Nouman Ali; Adeeba Ali; Muhammad Sheraz Yousuf; Arsheen Rehman; Saad Muhammad Islam; Bilal Ilyas; Aamir Ali (In Silico Pharmacology, 2025)

Development of empirical models for forecasting of global solar radiations for different climatic regions of Pakistan - Talha Bin Nadeem; Yousuf Baig; Muhammad Talha Ansari (Next Research, 2025)

Synthesis, Spectroscopic, Electronic and Molecular Docking Studies of Pyrazole Based Chalcones as Potential Anticancer Agents - Noreen Aslam; Muhammad Ibrahim; Afifa Yousuf; Muhammad Arif Ali; Jonathan M. White; Ansa Madeeha Zafar; Mussarat Jabeen; Misbahul Ain Khan (Journal of Fluorescence, 2025)

Ore genesis and critical metal enrichment using deep learning algorithms in Gunga Pb-Zn deposit, Southern Pakistan: Constraints from sphalerite geochemistry and isotopic compositions - Muhammad A. Gul; Huishan Zhang; Yu Yang; Guangli Ren; Chao Sun; Xiaojian Zhao; Tahir Bin Yousuf; Ahmed Shah; Rizwan Sarwar Awan; Mohamed Faisal; Xiaoyong Yang (Journal of Geochemical Exploration, 2025)

Structural Traits Driving Water Hyacinth (Eichhornia crassipes) Aggressive Spread and Ecosystem Disruption - Ummar Iqbal; Abdul Wahab; Sadaf Rafiq; Sibgha Noreen; Sana Abid; Muhammad Sharif; Mehboob Ahmad; Muhammad Yousuf (Water, Air, & Soil Pollution, 2025)

Assessing the impact of air pollution on global and diffuse solar radiation in Karachi, Pakistan: a comparative analysis of multiple linear regression and artificial neural network models - Muhammad Uzair Yousuf; Abid Ali; Muhammad Umair (Theoretical and Applied Climatology, 2025)

Prediction of nitrate concentration and the impact of land use types on groundwater in the Nansi Lake Basin - Javed Iqbal; Chunli Su; Hasnain Abbas; Jiaqi Jiang; Zhantao Han; Muhammad Yousuf Jat Baloch; Xianjun Xie (Journal of Hazardous Materials, 2025)

Life cycle assessment of lignite-fueled ultra-supercritical coal-fired power plant with evaluation of solar energy integration - Muhammad Uzair Yousuf; Mubashir Ali Siddiqui; Munesh Kumar; Muhammad Umair (Fuel, 2025)

Performance and data acquisition from low-cost air quality sensors: a comprehensive review - Mubashir Ali Siddiqui; Mirza Hammad Baig; Muhammad Uzair Yousuf (Air Quality, Atmosphere & Health, 2025)

Thriving in extremes: Adaptability potential of desert cotton Aerva javanica to hyper-arid saline conditions - Ummar Iqbal; Sana Abid; Muhammad Sharif; Sadaf Rafiq; Abdul Wahab; Mehboob Ahmad; Muhammad Yousuf (Journal of Arid Environments, 2025)

Phytoremediation Capacity of Saltwort (Salsola imbricata Forssk.) Determined by Tissue Organization and Physio-biochemical traits under Arid Saline Environments - Ummar Iqbal; Muhammad Sharjeel Arif; Muhammad Sharif; Abdul Wahab; Mehboob Ahmad; Muhammad Yousuf; Sadaf Rafiq; Sana Abid (Water, Air, & Soil Pollution, 2025)

Exploring heat transfer in freezing supercooled water droplet through high-speed infrared thermography - Hassan Abbas Khawaja; Samaneh Keshavarzi; Adeel Yousuf; Manaf Muhammed; Muhammad Shakeel Virk; Derek Harvey; Gelareh Momen (Cold Regions Science and Technology, 2025)

Impact of synbiotic on growth performance, histo-architectural modulation of lymphoid organ, hematology, blood biochemistry and humoral immune response in naked neck chicken - Hemayet Hossain; Harimurti Nuradji; Mohammad Yousuf Miah; Muhammad Nazrul Islam; Md. Saiful Islam Siddiqui (Tropical Animal Health and Production, 2025)

A critical review of NO2 and AOD in major Asian cities: challenges, mitigation approaches and way forwards - Most Mastura Munia Farjana Jion; Abu Reza Md Towfiqul Islam; Mahir Shahrier; Md Yousuf Mia; Jannatun Nahar Jannat; Md Arfan Ali; Md Abdullah Al Masud; Md Firoz Khan; Muhammad Bilal; Abubakr M. Idris; Guilherme Malafaia (Air Quality, Atmosphere & Health, 2025)

Unveiling the sweetness: evaluating yield and quality attributes of early generation sweet corn (Zea mays subsp. sachharata) inbred lines through morphological, biochemical and marker-based approaches - Shah Mohammad Usman; Raheel Shafeeq Khan; Asif Bashir Shikari; Nida Yousuf; Showkat Ahmad Waza; Shabir Hussain Wani; Muhammad Ashraf Bhat; F. Shazia; Faroq Ahmad Sheikh; Asma Majid (Molecular Biology Reports, 2024)

Exposure Levels, Health Risks, Spatially Distribution, Multivariate Statistics and Positive Matrix Factorization Model of Heavy Metals from Wild solid Waste Dumpsites - Predrag Ilić; Svetlana Ilić; Abdur Rashid; Zain Mushtaq; Sanja Mrazovac Kurilić; Ljiljana Stojanović Bjelić; Dragana Nešković Markić; Zia Ur Rahman Farooqi; Muhammad Yousuf Jat Baloch; Tariq Mehmood; Zahid Ullah; Sobia Riaz (Water, Air, & Soil Pollution, 2024)

Multi-biological risk in groundwater-surface water system under landfill stress: Driven by bacterial size and biological toxicity - Juanfen Chai; Wenjing Zhang; Kaichao Zhao; Shuxin Li; Muhammad Yousuf Jat Baloch; Zezheng Wang; Dayi Zhang; Yuesuo Yang (Journal of Hydrology, 2024)

Impact of extreme weather events on mental health in South and Southeast Asia: A two decades of systematic review of observational studies - Muhammad Mainuddin Patwary; Mondira Bardhan; Md Atiqul Haque; Syed Moniruzzaman; Johanna Gustavsson; Md Maruf Haque Khan; Jenni Koivisto; Marium Salwa; Saidur Rahman Mashreky; A.K.M. Fazlur Rahman; Anika Tasnim; Md Redwanul Islam; et al. (Environmental Research, 2024)

Miniaturizing Power: Harnessing Micro-Supercapacitors for advanced micro-electronics - Qazi Muhammad Saqib; Abdul Mannan; Muhammad Noman; Mahesh Y. Chougale; Chandrashekhar S. Patil; Youngbin Ko; Jungmin Kim; Swapnil R. Patil; Muhammad Yousuf; Rayyan Ali Shaukat; Young Pyo Jeon; Deepak Dubal; et al. (Chemical Engineering Journal, 2024)

Application of Synthetic Iron Oxyhydroxide with Influencing Factors for Removal of As(V) and As(III) from Groundwater - Shakeel Ahmed Talpur; Muhammad Yousuf Jat Baloch; Chunli Su; Javed Iqbal; Aziz Ahmed; Hafeez Ahmed Talpur (Journal of Earth Science, 2024)

Comprehensive characterization of unscientifically disposed municipal solid waste (MSW) in Kashmir Region, India - Muneeb Farooq; Adhithiya Venkatachalapati Thulasiraman; Zahoor Manzoor; Sachin Tripathi; Farhat Un Nisa; Asif Farooq; Saheem Rasool; Reyaz Hussain Akhoon; Muhammad Yousuf Shah; Khalid Muzamil Gani (Environmental Monitoring and Assessment, 2024)

Brown macro-seaweeds derived agro-biostimulant for Zea mays farming in saline conditions: Growth enhancement and optimum biochemical and ion feedback - Sadaf Gul; Muhammad Farrakh Nawaz; Muhammad Talha Bin Yousaf; Muhammad Haroon U Rashid; Muhammad Yousuf Adnan; Shamama Tausif; Arooj Javed; Zainul Abideen; Ali El- Keblawy (Biocatalysis and Agricultural Biotechnology, 2024)

Remimazolam versus propofol for sedation in gastrointestinal endoscopy and colonoscopy within elderly patients: a meta-analysis of randomized controlled trials - Wania Ahmer; Sahar Imtiaz; Daniyal Muhammad Alam; Khadija Ahmed; Barka Sajid; Juvairia Yousuf; Sunny Asnani; Muhammad Ahmed Ali Fahim; Rahmeen Ali; Marium Mansoor; Muhammad Talha Safdar; Muhammad Umair Anjum; et al. (European Journal of Clinical Pharmacology, 2024)

A review of infrared thermography applications for ice detection and mitigation - Adeel Yousuf; Hassan Khawaja; Muhammad S. Virk (Cold Regions Science and Technology, 2024)

A comparison of experimental and computational methods for circular footing response on lime-treated geotextile reinforced silty sand - Syed Md Yousuf; Mehboob Anwar Khan; Syed Muhammad Ibrahim; Anil Kumar Sharma; Furquan Ahmad; Pramod Kumar (Modeling Earth Systems and Environment, 2024)

E. coli phage transport in porous media: Response to colloid types and water saturation - Wenjing Zhang; Shuxin Li; Kaichao Zhao; Juanfen Chai; Bo Wan; Yunqi Qin; Huan Huan; Simiao Sun; Yuesuo Yang; Muhammad Yousuf Jat Baloch (Science of The Total Environment, 2024)

Hydrogeochemistry and prediction of arsenic contamination in groundwater of Vehari, Pakistan: comparison of artificial neural network, random forest and logistic regression models - Javed Iqbal; Chunli Su; Maqsood Ahmad; Muhammad Yousuf Jat Baloch; Abdur Rashid; Zahid Ullah; Hasnain Abbas; Anam Nigar; Asmat Ali; Arif Ullah (Environmental Geochemistry and Health, 2024)

Expression Studies of Synthetic Sucrose Isomerase Gene 1 (SySIG1) in Saccharum officinarum L - Mudassar Fareed Awan; Sajed Ali; Irfan Ullah; Amin Ullah; Muhammad Tariq; Muhammad Shahzad Iqbal; Aisha Khalid; Sana Fatima; Yousuf Shafiq; Idrees Ahmad Nasir; Muhammad Muzammal; Arshad Farid (Plant Molecular Biology Reporter, 2023)

Corrigendum to “Terrestrial and groundwater storage characteristics and their quantification in the Chitral (Pakistan) and Kabul (Afghanistan) river basins using GRACE/GRACE-FO satellite data” - Aqil Tariq; Shoaib Ali; Iqra Basit; Ahsan Jamil; Nizom Farmonov; Behnam Khorrami; Muhammad Mohsin Khan; Samira Sadri; Muhammad Yousuf Jat Baloch; Fakhrul Islam; Muhammad Bilawal Junaid; Wesam Atef Hatamleh; et al. (Groundwater for Sustainable Development, 2023)

Terrestrial and groundwater storage characteristics and their quantification in the Chitral (Pakistan) and Kabul (Afghanistan) river basins using GRACE/GRACE-FO satellite data - Aqil Tariq; Shoaib Ali; Iqra Basit; Ahsan Jamil; Nizom Farmonov; Behnam Khorrami; Muhammad Mohsin Khan; Samira Sadri; Muhammad Yousuf Jat Baloch; Fakhrul Islam; Muhammad Bilawal Junaid; Wesam Atef Hatamleh (Groundwater for Sustainable Development, 2023)

Conceptual design of cost-effective ice detection system based on infrared thermography - Adeel Yousuf; Hassan Khawaja; Muhammad S. Virk (Cold Regions Science and Technology, 2023)

Unraveling the potential of microbes in decomposition of organic matter and release of carbon in the ecosystem - Taqi Raza; Muhammad Farhan Qadir; Khuram Shehzad Khan; Neal S. Eash; Muhammad Yousuf; Sumanta Chatterjee; Rabia Manzoor; Sana ur Rehman; Joel Nathaniel Oetting (Journal of Environmental Management, 2023)

Assessment of landcover impacts on the groundwater quality using hydrogeochemical and geospatial techniques - Javed Iqbal; Gomal Amin; Chunli Su; Ehsan Haroon; Muhammad Yousuf Jat Baloch (Environmental Science and Pollution Research, 2023)

Seaweed-derived bio-stimulant improves growth and salt tolerance of radish varieties under saline conditions - Sadaf Gul; Zainul Abideen; Muhammad Yousuf Adnan; Maria Hanif; Muhammad Farrakh Nawaz; Shumaila; Ali El- Keblawy (Biocatalysis and Agricultural Biotechnology, 2023)

Estimating Photosynthetically Active Euphotic Layer in Major Lakes of Kumaun Region Using Secchi Depth - Zainab Khan; Sk Ajim Ali; Mohammad Mohsin; Syed Kausar Shamim; Ekaterina Mankovskaya; Farhana Parvin; Nikhat Bano; Ateeque Ahmad; Muhammad Yousuf Jat Baloch (Water, Air, & Soil Pollution, 2023)

Correction: Ascorbic and Salicylic Acids Vitalized Growth, Biochemical Responses, Antioxidant Enzymes, Photosynthetic Efciency, and Ionic Regulation to Alleviate Salinity Stress in Sorghum bicolor - Muhammad Azeem; Robina Sultana; Athar Mahmood; Muhammad Qasim; Zamin Shaheed Siddiqui; Sahar Mumtaz; Talha Javed; Muhammad Umar; M. Yousuf Adnan; Manzer H. Siddiqui (Journal of Plant Growth Regulation, 2023)

Major challenges in widespread adaptation of aerobic rice system and potential opportunities for future sustainability - Muhammad Shahbaz Farooq; Hira Fatima; Obaid Ur Rehman; Muhammad Yousuf; Rabia Kalsoom; Sajid Fiaz; Muhammad Ramzan Khan; Muhammad Uzair; Shuhao Huo (South African Journal of Botany, 2023)

Ascorbic and Salicylic Acids Vitalized Growth, Biochemical Responses, Antioxidant Enzymes, Photosynthetic Efficiency, and Ionic Regulation to Alleviate Salinity Stress in Sorghum bicolor - Muhammad Azeem; Robina Sultana; Athar Mahmood; Muhammad Qasim; Zamin Shaheed Siddiqui; Sahar Mumtaz; Talha Javed; Muhammad Umar; M. Yousuf Adnan; Manzer H. Siddiqui (Journal of Plant Growth Regulation, 2023)

A critical review and prospect of NO2 and SO2 pollution over Asia: Hotspots, trends, and sources - Most. Mastura Munia Farjana Jion; Jannatun Nahar Jannat; Md. Yousuf Mia; Md. Arfan Ali; Md. Saiful Islam; Sobhy M. Ibrahim; Subodh Chandra Pal; Aznarul Islam; Aniruddha Sarker; Guilherme Malafaia; Muhammad Bilal; Abu Reza Md Towfiqul Islam (Science of The Total Environment, 2023)

Arsenic Removal from Groundwater Using Iron Pyrite: Influence Factors and Removal Mechanism - Muhammad Yousuf Jat Baloch; Chunli Su; Shakeel Ahmed Talpur; Javed Iqbal; Kulvinder Bajwa (Journal of Earth Science, 2023)

Revisiting the environmental impact of renewable energy, non-renewable energy, remittances, and economic growth: CO2 emissions versus ecological footprint for top remittance-receiving countries - Muhammad Umair; Muhammad Uzair Yousuf; Jabbar Ul-Haq; Zahid Hussain; Hubert Visas (Environmental Science and Pollution Research, 2023)

A novel approach for power enhancement of vertical mounted bifacial photovoltaic system using reflecting mirrors - Muhammad Aleem Zahid; Hasnain Yousuf; Youngkuk Kim; Junsin Yi; Suresh Kumar Dhungel (Journal of Cleaner Production, 2023)

Migration risk of Escherichia coli O157:H7 in unsaturated porous media in response to different colloid types and compositions - Shuxin Li; Wenjing Zhang; Dayi Zhang; Wei Xiu; Shengyu Wu; Juanfen Chai; Jincai Ma; Muhammad Yousuf Jat Baloch; Simiao Sun; Yuesuo Yang (Environmental Pollution, 2023)

Phenotypic and Genotypic Analysis of the Population of Phytophthora infestans in Bangladesh Between 2014 and 2019 - Md. Huzzatul Islam; Sangee Sarkar Shanta; Muhammad Iqbal Hossain; Muhammed Ali Hossain; Md. Monower Hossain; Ebna Habib Md. Shofiur Rahaman; Abdullah Al Mahmud; Md. Abdullah Yousuf Akhond; Louise Sullivan; David E. L. Cooke; Geert J. T. Kessel; Louise R. Cooke; et al. (Potato Research, 2023)
In Bangladesh, the third largest producer of potatoes in Asia, late blight, caused by Phytophthora infestans , is the major constraint to production. Nevertheless, there is a lack of published information on the pathogen population. A collection of 69 isolates obtained from samples of infected potato foliage collected in 2018–2019 varied significantly in their aggressiveness to detached potato leaflets and tuber slices of cv. Diamant. On leaflets, most isolates were highly aggressive, colonizing more than half the surface in 7 days. On tuber slices, while some isolates were highly aggressive, those collected in 2019 were less so. There was a significant effect of the locations from which the isolates were obtained on aggressiveness to both leaflets and tuber slices, but aggressiveness to leaflets and to tuber slices was not significantly correlated. All isolates were A2 mating type and either intermediate (38%) or resistant (62%) in sensitivity to the fungicide metalaxyl . A subset of 24 isolates all had mitochondrial DNA haplotype Ia. Samples of P. infestans DNA (124) from infected potato foliage obtained from Bangladesh (2014–2019) were genotyped by 12-plex SSR. The vast majority (95%) were assigned to EU_13_A2, which was present in every year in which samples were collected. Numerous EU_13_A2 variants were identified, many specific to Bangladesh. Six samples (from 2017 to 2019) had genotypes distinct from EU_13_A2 and with no close match to known European lineages. It is concluded that the current P. infestans population of Bangladesh is dominated by the aggressive lineage EU_13_A2, also dominant in India and Pakistan. The implications of this for control of late blight are discussed.

Groundwater fluoride and nitrate contamination and associated human health risk assessment in South Punjab, Pakistan - Javed Iqbal; Chunli Su; Mengzhu Wang; Hasnain Abbas; Muhammad Yousuf Jat Baloch; Junaid Ghani; Zahid Ullah; Md. Enamul Huq (Environmental Science and Pollution Research, 2023)

Evaluating the symmetric and asymmetric effects of fossil fuel energy consumption and international capital flows on environmental sustainability: a case of South Asia - Muhammad Umair; Muhammad Uzair Yousuf (Environmental Science and Pollution Research, 2022)

Energy, exergy, economic, environmental, energoeconomic, exergoeconomic, and enviroeconomic (7E) analyses of wind farms: a case study of Pakistan - Muhammad Uzair Yousuf; Muhammad Adil Abbasi; Muhammad Kashif; Muhammad Umair (Environmental Science and Pollution Research, 2022)

Use of Eudragit RS PO, HPMC K100M, Ethyl Cellulose, and Their Combination for Controlling Nicorandil Release from the Bilayer Tablets with Atorvastatin as an Immediate-Release Layer - Wajiha Iffat; Muhammad Harris Shoaib; Rabia Ismail Yousuf; Faaiza Qazi; Zafar Alam Mahmood; Iyad Naeem Muhammad; Kamran Ahmed; Farrukh Rafiq Ahmed; Muhammad Suleman Imtiaz (Journal of Pharmaceutical Innovation, 2022)

Sub-lethal effects of organophosphates and synthetic pyrethroid insecticides on muscle tissue transaminases of Oreochromis niloticus in vivo - Muhammad Amin; Masarrat Yousuf; Naveed Ahmad; Mohammad Attaullah; Muhammad Ikram; Attia A. Abou Zaid; Clement Ameh Yaro; Eida M. Alshammari; Yaser S. Binnaser; Gaber El-Saber Batiha; Islam Dad Buneri (Toxicological Research, 2022)

New bioactive monoterpene indole alkaloid from Rinorea yaundensis Engl. - Bushra Khatoon; Sadia Zikr Ur Rehman; Sammar Yousuf; Mehreen Lateef; Martial Flora Adjapmoh Essombo; Alain Francois Kamdem Waffo; Muhammad Shaiq Ali (Natural Product Research, 2022)

Growth regulation of Desmostachya bipinnata by organ-specific biomass, water relations, and ion allocation responses to improve salt resistance - Muhammad Yousuf Adnan; Tabassum Hussain; Muhammad Zaheer Ahmed; Bilquees Gul; M. Ajmal Khan; Brent L. Nielsen (Acta Physiologiae Plantarum, 2021)

An ensemble procedure for pattern recognition of regional drought - Zulfiqar Ali; Ijaz Hussain; Muhammad Faisal; Muhammad Yousuf Shad; Elsayed E. Elashkar; Showkat Gani (International Journal of Climatology, 2020)
Drought being a complex natural hazard is challenging to monitor. Although standardized procedures for drought characterization are commonly used, the uncertainty about accurate drought characterization under various procedures always exists. Therefore, for effective drought mitigation policies, it is necessary to compare the performance of new and the existing drought procedures. In this study, we proposed a new procedure— The Drought Intensity Pattern Determinate (DIPD) to examine and compare the spatial‐temporal intensities of various drought episodes based on Standardized Drought Indices (SDI). The DIPD framework provides a new tool— The Drought Concentration Index ( DCI ) to understand the annual intensity of drought classes by alluding the observed frequencies of drought episodes. At the preliminary level of assessment, DIPD is employed at 52 meteorological stations of Pakistan, and compared three commonly used standardized drought indices: Standardized Precipitation Index (SPI), Standardized Evapotranspiration Index (SPEI) and Standardized Precipitation Temperature Index (SPTI). Exploratory analysis shows a mixed picture as all the drought indices behaving similar for some patterns of drought classes, while some classes show significant discrepancies. In addition, we assessed and compared the spatial distributions using spatial Poisson lognormal model by assuming SDI as a non‐Gaussian process for individual total classes of observed DCI. Results show that the proposed method has ability to incorporate the inner variability in patterns of drought classes. In summary, the DIPD provided a new regional based comparative framework, which accounts the all possible episodes of drought classes and effect of inner discrepancies among quantitative values of SDI.

Effect of breeding method and season on pregnancy rate and embryonic and fetal losses in lactating Nili-Ravi buffaloes - Arslan Qayyum; Usman Arshad; Muhammad Rizwan Yousuf; Nasim Ahmad (Tropical Animal Health and Production, 2018)

Nitrogen-regulated changes in total amino acid profile of maize genotypes having contrasting response to nitrogen deficit - Arshid Hussain Ganie; Altaf Ahmad; Peerzada Yasir Yousuf; Renu Pandey; Sayeed Ahmad; Ibrahim M Aref; Muhammad Iqbal (Protoplasma, 2017)

A long-term trend in precipitation of different spatial regions of Bangladesh and its teleconnections with El Niño/Southern Oscillation and Indian Ocean Dipole - Md. Kawser Ahmed; Mohammad Samsul Alam; Abu Hena Muhammad Yousuf; Md. Monirul Islam (Theoretical and Applied Climatology, 2017)

Salt-stress-responsive chloroplast proteins in Brassica juncea genotypes with contrasting salt tolerance and their quantitative PCR analysis - Peerzada Yasir Yousuf; Altaf Ahmad; Ibrahim M. Aref; Munir Ozturk; Hemant; Arshid Hussain Ganie; Muhammad Iqbal (Protoplasma, 2016)

Salt stress-induced modulations in the shoot proteome of Brassica juncea genotypes - Peerzada Yasir Yousuf; Altaf Ahmad; Arshid Hussain Ganie; Muhammad Iqbal (Environmental Science and Pollution Research, 2016)

Erratum to: Synthesis crystal structure of 2-methoxybenzoylhydrazones and evaluation of their α-glucosidase and urease inhibition potential - Muhammad Taha; Nor Hadiani Ismail; Mohd Syukri Baharudin; Salima Lalani; Sadia Mehboob; Khalid Mohammed Khan; Sammer Yousuf; Salman Siddiqui; Fazal Rahim; M. Iqbal Choudhary (Medicinal Chemistry Research, 2015)

Synthesis crystal structure of 2-methoxybenzoylhydrazones and evaluation of their α-glucosidase and urease inhibition potential - Muhammad Taha; Nor Hadiani Ismail; Mohd Syukri Baharudin; Salima Lalani; Sadia Mehboob; Khalid M. Khan; Sammer yousuf; Salman Siddiqui; Fazal Rahim; M. Iqbal Choudhary (Medicinal Chemistry Research, 2015)

Changes in extreme temperature and precipitation in the Arab region: long‐term trends and variability related to ENSO and NAO - M. G. Donat; T. C. Peterson; M. Brunet; A. D. King; M. Almazroui; R. K. Kolli; Djamel Boucherf; Anwar Yousuf Al‐Mulla; Abdourahman Youssouf Nour; Ahmed Attia Aly; Tamer Ali Ali Nada; Muhammad M. Semawi; et al. (International Journal of Climatology, 2014)
A workshop was held in Casablanca, Morocco, in March 2012, to enhance knowledge of climate extremes and their changes in the Arab region. This workshop initiated intensive data compilation activities of daily observational weather station data from the Arab region. After conducting careful control processes to ensure the quality and homogeneity of the data, climate indices for extreme temperatures and precipitation were calculated. This study examines the temporal changes in climate extremes in the Arab region with regard to long‐term trends and natural variability related to ENSO and NAO . We find consistent warming trends since the middle of the 20th Century across the region. This is evident in the increased frequencies of warm days and warm nights, higher extreme temperature values, fewer cold days and cold nights and shorter cold spell durations. The warming trends seem to be particularly strong since the early 1970s. Changes in precipitation are generally less consistent and characterised by a higher spatial and temporal variability; the trends are generally less significant. However, in the western part of the Arab region, there is a tendency towards wetter conditions. In contrast, in the eastern part, there are more drying trends, although, these are of low significance. We also find some relationships between climate extremes in the Arab region and certain prominent modes of variability, in particular El Niño‐Southern Oscillation ( ENSO ) and North Atlantic Oscillation ( NAO ). The relationships of the climate extremes with NAO are stronger, in general, than those with ENSO , and are particularly strong in the western part of the Arab region (closer to the Atlantic Ocean). The relationships with ENSO are found to be more significant towards the eastern part of the area of study. © 2013 Royal Meteorological Society

Development and Evaluation of Hydrophilic Colloid Matrix of Famotidine Tablets - Muhammad Harris Shoaib; Saniah Al Sabah Siddiqi; Rabia Ismail Yousuf; Kamran Zaheer; Muhammad Hanif; Saeed Rehana; Sabahat Jabeen (AAPS PharmSciTech, 2010)